Academic integrity - concept, content and ways of violating it - Ćorić, Dragana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
academic integrity is one of the most important pillars of higher education. It combines the demand for perseverance and honesty in research that contributes to the development of science; the demand for collegial appreciation and respect for the work of members of the academic community, without discrimination, disparagement or denial of academic freedom; the demand to spread a good ethical example of work and success only on the basis of honorable, honest and persistent work; and finally the demand to accept minimum norms of ethical behavior that can only protect all members of the academic community, not harm them. Put in this way, academic integrity is not just a mere sum of some rules of conduct, which should be respected, mostly because of the fear of punishment for their violation, but it goes beyond its own concept and becomes a way of life for the members of the academic community. The work presents an overview of the meaning of integrity in general, of academic integrity and of ways of violating it and should be understood as a tribute to the efforts of the academic community to regain the place and importance it had before in society.